PERANCANGAN MESIN OVEN HEAT TREATMENT DENGAN KAPASITAS 1200 WATT SKALA PRAKTIKUM - Achmad Soleh; Wisma Soedarmadji; Mohammad Effendy (Prodi Teknik Mesin Universitas Yudharta, 2022)
A heat treatment oven is a machine used to heat metal materials, with a predetermined temperature. change the physical properties of the metal by a controlled heating process. Yudharta Pasuruan University itself is constrained by the limitations of the tools that make it difficult for students to apply directly, one of which is the heat treatment practicum. With the existing obstacles, the author made a simple and useful heat treatment oven for practical application at Yudharta University, Pasuruan. To produce the required mechanical properties, it is necessary to apply heat treatment. For this reason, the author made a Redesign of the Heat Treatment Oven Machine with a Capacity of 1200 Watt, which has dimensions of 29 cm Height, 29 cm Width, and 52 cm Length. The advantage of this oven is that it generates heat using an electric coil element. The drawback is that this machine cannot be operated, if the electrical power used is below 1200 watts. This study uses the design method, the results of this study obtained the volume of the combustion chamber with dimensions of height 235 mm x width 235 mm x length 455 mm, total weight 101,834 kg with a maximum temperature of 900â„ƒ, the heating wire used is nichrome Ni 80 type wire which has a resistance 81 ohms with a length of 9.5 meters, wire cross-sectional area 11.7 x 10-8.